Effect of the Age and Body Weight of the Broiler Breeders Male on the Presentation of Oxidative Stress and Its Correlation with the Quality of Testicular Parenchyma and Physiological Antioxidant Levels - Magdalena Escorcia; Félix Sánchez-Godoy; David Ramos-Vidales; Omar Noel Medina-Campos; José Pedraza-Chaverri (Veterinary Sciences, 2020)
Chicken meat is a food of high nutritional quality; its production requires birds called broilers breeders and looking after all aspects that influence their reproductive capacity. An ongoing controversy exists among researchers related to the weight of the rooster and its fertilization capacity. By histological and biochemical tests, the association between weight and age with oxidant damage, testicular parenchyma and antioxidant capacity was evaluated in Ross 308 roosters. Testicular integrity was assessed by histological analysis, oxidative stress was determined by malondialdehyde content, non-enzymatic antioxidant capacity was determined by oxygen radical absorbance capacity assay and enzymatic antioxidant capacity through glutathione peroxidase, glutathione reductase and glutathione-S-transferase activities. Histological analysis showed vacuolization of the epithelium from the seminiferous tubules. A significant negative association was observed between malondialdehyde and the deterioration of the integrity of the seminiferous epithelium, as well as between age and integrity of the seminiferous epithelium. It became evident that oxidative damage directly affects the quality of testicular parenchyma. Weight and age were not associated with the antioxidant enzymes activities, but with non-enzymatic capacity. The data obtained suggest that weight is not the most important factor that influences the fertility of the rooster.